MB09, a denosumab biosimilar candidate: Biosimilarity demonstration in a phase I study in healthy subjects - Monika Tomaszewska‐Kiecana; Elisabete Carapuça; Amalia Florez‐Igual; Javier Queiruga‐Parada (Clinical and Translational Science)
Abstract This was a Phase I, randomized, double‐blinded, three‐arm, single‐dose, parallel study aimed to demonstrate pharmacokinetic (PK) similarity between MB09 (a denosumab biosimilar candidate) and reference denosumab (XGEVA® from European Union [EU‐reference] and United States [US‐reference]) in a healthy male population. The primary PK endpoints included: Area under the serum concentration versus time curve from time 0 to the last quantifiable concentration timepoint (AUC0–last); and maximum observed serum concentration (Cmax). Secondary endpoints included: AUC from time 0 extrapolated to infinity (AUC0–∞), time to reach maximum observed concentration, clearance, terminal phase half‐life, pharmacodynamic, safety, and immunogenicity assessments. A total of 255 subjects were randomized (1:1:1) to receive a subcutaneous 35 mg dose of MB09 or reference denosumab. Cmax was reached after denosumab administration, followed by a decline in the concentration with similar terminal phase half‐live across treatment arms. Systemic exposure of MB09 (AUC0–last and Cmax) was equivalent to the reference denosumab, as the 90% confidence intervals around the geometric least square mean ratios laid within the predefined acceptance limits (80.00%, 125.00%) across all comparisons. Pharmacodynamic parameters, based on the percent of change from baseline in serum C‐terminal telopeptide of Type 1 collagen levels, were similar across the three arms. The treatments were considered safe and generally well tolerated, with 92 treatment‐emergent adverse events reported (most Grade 2 and 3) and similarly distributed. Immunogenicity was low and similarly distributed. These results provide strong evidence that supports the biosimilarity between MB09 and denosumab reference products.